GEOLOGI DAN ANALISIS JENIS BATUAN ASAL PADA PEMBENTUKAN ENDAPAN NIKEL LATERIT DI KECAMATAN BUNTA, KABUPATEN BANGGAI - Yuriadi, Bilal Aditya; Arifin, Yayu Indriati; Hutagalung, Ronal (Universitas Negeri Makassar, 2024)
This research is motivated by the presence of nickel laterite deposit potential originating from various types of lithology in the Bunta sub-district, Banggai Regency, which needs to be followed up to facilitate exploration of nickel laterite. The research area is located at coordinates 122°15'8